Floating simulator with a single DVCCTA - Tangsrirat, Worapong (My University, 2013)
In this paper, a simple circuit configuration for simulating the floating inductor, capacitor and resistor using differential voltage current conveyor transconductance amplifier (DVCCTA) as an active element has been presented. The proposed floating simulator circuit uses only one DVCCTA and two grounded passive elements, and can realize floating inductor, capacitor or resistor depending on the passive element selection. The equivalent value of the realized simulator can be tuned electronically through the transconductance parameter of the DVCCTA. The circuit also does not require any realization conditions. The proposed circuit together with its applications is demonstrated using PSPICE simulation with 0.5 μm MIETEC CMOS technology.
Keywords: Capacitance multiplier; Differential voltage current conveyor transconductance amplifier (DVCCTA); Floating simulator; Inductance simulation